Role of anthocyanin traits on the impact of oenological tannins addition in the first stage of red winegrape skin simulated maceration. (1st August 2020) - Paissoni, Maria Alessandra; Río Segade, Susana; Carrero-Carralero, Cipriano; Montanini, Carlo; Giacosa, Simone; Rolle, Luca
Highlights: Grape-derived tannins enhanced polymer pigment formation in first maceration stage. Quebracho-derived tannins increased disubstituted anthocyanin content. Tannin addition modified color parameters depending on the variety. Exogenous tannins addition can be tailored on the varietal anthocyanin profile. Abstract: In winemaking, exogenous tannins are added before maceration to improve future wine color characteristics derived from extracted grape anthocyanins. The study aimed to investigate the relation between different grape varieties, selected according to their anthocyanin profile, and the effect of five exogenous tannin formulations differing in origin and chemical features. Anthocyanin content, polymeric pigments, and color traits were assessed during a 72-hour skin simulated maceration. Grape skin-derived tannins increased color intensity (up to one unit) and polymeric pigments formation (up to 6.5%) in malvidin-prevalent Merlot and Cabernet sauvignon, with different extent depending on the anthocyanin richness. Grape seed-derived and ellagic formulations favored the pigment polymerization, the first in Nebbiolo and Sangiovese (up to 8.2%), which are characterized by high ratios of disubstituted anthocyanins, and the latter in malvidin-rich Syrah and Aglianico (up to 5%). A positive effect of quebracho regarded the defense of anthocyanin forms, particularly in Sangiovese and Nebbiolo.